Ox-LDL Influences Peripheral Th17/Treg Balance by Modulating Treg Apoptosis and Th17 Proliferation in Atherosclerotic Cerebral Infarction - Li, Qing; Wang, Yiping; Li, Hongqi; Shen, Guodong; Hu, Shilian (Cellular physiology and biochemistry, 2014)
Background: CD4 + CD25 + regulatory T (Treg) cells and T-helper 17 (Th17) cells play important roles in acute cerebral infarction (ACI). Our previous findings have suggested that oxidized low-density lipoprotein (Ox-LDL) could influence Treg/Th17 ratio in ACI patients. However, the mechanisms are still not clear. Methods and Results: We evaluated the effects of ox-LDL on Th17/Treg cell apoptosis and proliferation in vitro. Our results demonstrated that with increased ox-LDL concentrations, the frequency and suppressive function of Treg cells was decreased while the frequency of Th17 cells was elevated in control subjects. In addition, AnnexinV + apoptotic rate, Fas/Fas ligand (FasL) expression, and Caspase-3 activity were escalated in Treg cells while were no significant changes in Th17 cells. Simultaneously, 5-Bromo-29-Deoxyuridine (BrdU) and 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyl Tetrazolium Bromide (MTT) incorporation of Th17 cells was elevated accompanied by upregulated nuclear factor-κB (NF-κB) activity. However, Th17 proliferation was decreased when pre-incubated with Pyrrolidine dithiocarbamate (PDTC, inhibitor of NF-κB activation). Furthermore, there were significant changes induced by ox-LDL in Treg apoptosis, Fas/FasL/Caspase-3 expression of Treg cells, and Th17 proliferation, NF-κB activation of Th17 in ACI patients than in patients with transient ischemic attack (TIA) and control subjects (P<0.01, P<0.05 respectively). Conclusion: These data support that ox-LDL may influence the Th17/Treg balance by modulating Fasmediated Treg apoptosis and NF-κB-associated Th17 proliferation. Ox-LDL also induced a more significant alteration of Treg and Th17 in ACI patients than in TIA and control groups, suggesting a novel role in the pathogenesis of ACI.